Pengaruh Persepsi Dukungan Organisasi pada Perilaku Kewargaan Organsasional dengan Kepuasan Kerja sebagai Variabel Intervening (Management Analysis Journal, 2015)
The purpose of this study was to find out th influence of the job satsfaction mediaton between the perceived organizatonal support variable toward the organizational citizenship behaviour employees of Perum Perhutani Unit ICentral Java.The population of this study were employees of Perum Perhutani Unit I Central Java as much 116 respondents using proportionale random sampling .The methods used in collecting the data was a questionnaire which was measured by likert scale. Analysis was partia test and The sobel analysis used SPSS 20 .The results of the study showed that thee was positive and significant impact between the perceived organizational support and job satisfaction, and also between perceived organizational support to the organizational citizenship behavior. The job satisfactionhad the mediation impact to therelation between the perceivedorganizational support and organizational citizenship behavior.The conclusion of this study was that perceived organizational support and job satisfaction played an importan trole in the on set of OCB. To show sthat OCB, the employee must have had a high perceived organizational support and job satisfaction in their work place